PETUNJUK TEKNIS DHARMA WACANA - I Made Arya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Dhamma Wacana activities are needed in order to spread the teachings of dharma, so that religious people not only know the rules of course, but also understand the nature of religion and understand tattwa, moral and ceremony. Dharma Wacana is as one method of guidance and guidance for the community among Hindus, apart from dharma sadana, dharma tula, dharma yatra, dharma yatra, dharma santi and dharma gita. The six methods of coaching are called sad dharma. The essence of the Dharma Wacana lies in the principle of speech which is called the teacher of kerokhanian which is derived from the teachings contained in the Vedic scriptures, both Veda Sruti and Veda Smerti, in the form of Veda Vakya as a message that must be guided in behavior in thinking, saying / saying and do. Every message contained in the discourse is expected to change his hearing behavior, and disseminated to the whole society, so that in his mind positiveimpact to the atmosphere of harmony of life, peace and welfare of mankind.Keywords: Dharma Wacana, Technical, DirectionsDhamma Wacana activities are needed in order to spread the teachings of dharma, sothat religious people not only know the rules of course, but also understand the nature of religionand understand tattwa, moral and ceremony. Dharma Wacana is as one method of guidance andguidance for the community among Hindus, apart from dharma sadana, dharma tula, dharmayatra, dharma yatra, dharma santi and dharma gita. The six methods of coaching are called saddharma. The essence of the Dharma Wacana lies in the principle of speech which is called theteacher of kerokhanian which is derived from the teachings contained in the Vedic scriptures,both Veda Sruti and Veda Smerti, in the form of Veda Vakya as a message that must be guided inbehavior in thinking, saying / saying and do. Every message contained in the discourse is expectedto change his hearing behavior, and disseminated to the whole society, so that in his mind positiveimpact to the atmosphere of harmony of life, peace and welfare of mankind.Keywords: Dharma Wacana, Technical, Directions